Association of match running performance with and without ball possession to football performance - Brito Souza, D.; López-Del Campo, R.; Blanco-Pita, H.; Resta, R.; Del Coso, J. (International Journal of Performance Analysis in Sport, 2020)
The aim of this study was to determine the relationship between match running patterns with and without ball possession and the number of points earned at the end of the Spanish football league (La Liga). Running distance covered with and without ball possession at speeds =21 and <21 km/h were analysed from 4 consecutive seasons (2015-2016 to 2018-2019). The league champion ran a shorter distance per match than the teams that classified for the Champions League (P = 0.05), than the teams ranked in the middle of the ranking (P = 0.02), and the teams that were relegated to the second division (P = 0.04). However, the league champion and the teams that classified for the Champions League ran a greater distance with ball possession than teams in the middle of the ranking (P < 0.01) and relegation teams (P < 0.01). A stepwise multiple regression analysis was able to explain only 37.9% of the total variance in the number of points with match running variables. In conclusion, the best football teams cover a greater distance with the ball than the less successful teams but the contribution of match running performance to overall football success is limited.